Aerobic Physical Training Attenuates Oxidative Stress in the Spinal Cord of Adult Rats Induced by Binge-like Ethanol Intake - Amanda do Nascimento Rodrigues; Diane Cleydes Baia da Silva; Daiane Claydes Baia-; Paulo Fernando Santos Mendes; Maria Karolina Martins Ferreira; Gabriel Sousa Rocha; Marco Aurelio M. Freire; Luanna Melo Pereira Fernandes; Cristiane do Socorro Ferraz Maia; Walace Gomes-Leal; Rafael Rodrigues Lima (MDPI AG, 2023)
Binge drinking is the most frequent consumption pattern among young adults and remarkably changes the central nervous system; thus, research on strategies to protect it is relevant. This study aimed to investigate the detrimental effects of binge-like EtOH intake on the spinal cord of male rats and the potential neuroprotective effects provided by moderate-intensity aerobic physical training. Male Wistar rats were distributed into the 'control group', 'training group', 'EtOH group', and 'training + EtOH'. The physical training protocol consisted of daily 30-min exercise on a treadmill for 5 consecutive days followed by 2 days off during 4 weeks. After the fifth day of each week, distilled water ('control group' and 'training group') or 3 g/kg of EtOH diluted at 20% w/v ('EtOH group' and 'training + EtOH group') was administered for 3 consecutive days through intragastric gavage to simulate compulsive consumption. Spinal cord samples were collected for oxidative biochemistry and morphometric analyses. The binge-like EtOH intake induced oxidative and tissue damage by decreasing reduced glutathione (GSH) levels, increasing lipid peroxidation (LPO), and reducing motor neurons (MN) density in the cervical segment. Even under EtOH exposure, physical training maintained GSH levels, reduced LPO, and prevented MN reduction at the cervical segment. Physical training is a non-pharmacological strategy to neuroprotect the spinal cord against oxidative damage induced by binge-like EtOH intake.